CONCEPTUALISING SHARIAH GOVERNANCE FOR HALAL HOTEL - Yudi Ahmad Faisal; Joeliaty; R. Rina Novianty Ariawaty; Egi Arvian Firmansyah (Ekonomi Islam, 2022)
This paper conceptualises a model of Shariah governance for halal hotels using Indonesia as a case study. Besides, it examines the roles and functions of the local Sharia standard-setting body within the national regulatory regime. One of the most important developments for the nascent halal hotel has been the efforts to establish Shariah governance, i.e., an overall process that governs the activities of halal hotels to comply with Shariah or Islamic law. This process may create clarity and consistency of Sharia rules for the halal hotel industry. The data analysis of this paper mainly comes from secondary sources of information either through existing rules or regulations of halal hotel, fatwas (Islamic legal verdicts), annual reports of the halal hotel, and other secondary materials. The originality of this research shows a model of Shariah governance for the halal hotel industry.  Keywords: Shariah Governance, Halal Hotel, Shariah Standard-Setting Body.